26 cm fall caught on video causing subdural hemorrhages and extensive retinal hemorrhages in an 8‐month‐old infant - Chris Brook; Waney Squier; Julie Mack (Clinical Case Reports, 2024)
Key Clinical Message Severe, too many to count retinal hemorrhages (RH) in infants have been associated with abusive head trauma, but can occur in short falls. An 8‐month‐old male fell backward from a height of 26 cm, landing on his buttocks then hitting the back of his head on a vinyl floor. The fall was videotaped. Acute subdural hemorrhages were found along with extensive, too many to count intra‐RH in both eyes. Falls from small heights on to the occiput can lead to extensive RH of the type often associated with abusive head trauma.